Determining early referral criteria for patients with suspected inflammatory arthritis presenting to primary care physicians: a cross-sectional study - Almoallim H (Dove Medical Press, 2017)
Hani Almoallim,1–3 Nahid Janoudi,2 Suzan M Attar,4 Mohammed Garout,5 Shereen Algohary,3 Muhammad Irfanullah Siddiqui,5 Hanan Alosaimi,3 Ashraf Ibrahim,3 Amira Badokhon,6 Zaki Algasemi7 1Department of Medicine, Medical College, Umm Alqura University, Makkah, 2Department of Medicine, Dr. Soliman Fakeeh Hospital, Jeddah, 3Alzaidi Chair of Research in Rheumatic Diseases, Medical College, Umm Alqura University, Makkah, 4Department of Medicine, King Abdulaziz University, Jeddah, 5Department of Community Medicine and Public Health, Umm Alqura University, Makkah, 6Administration of Public Health, Ministry of Health, Jeddah, 7Joint Program of Family and Community Medicine, Ministry of Health, Jeddah, Kingdom of Saudi Arabia Objective: Early diagnosis and initiation of treatment for inflammatory arthritis can greatly improve patient outcome. We aimed to provide standardized and validated criteria for use by primary care physicians (PCPs) in the identification of individuals requiring referral to a rheumatologist. Patients and methods: We analyzed the predictive value of a wide variety of demographic variables, patient-reported complaints, physical examination results, and biomarkers in order to identify the most useful factors for indicating a requirement for referral. Patients for this cross-sectional study were enrolled from various centers of the city of Jeddah, Saudi Arabia, if they were ≥18 years of age and presented to a PCP with small joint pain that had been present for more than 6 weeks. A total of 203 patients were enrolled, as indicated by the sample size calculation. Each patient underwent a standardized physical examination, which was subsequently compared to ultrasound findings. Biomarker analysis and a patient interview were also carried out. Results were then correlated with the final diagnosis made by a rheumatologist. Results: A total of 9 variables were identified as having high specificity and good predictive value: loss of appetite, swelling of metacarpophalangeal joint 2 or 5, swelling of proximal inter-phalangeal joint 2 or 3, wrist swelling, wrist tenderness, a positive test for rheumatoid factor, and a positive test for anti-citrullinated protein antibodies. Conclusion: Nine variables should be the basis of early referral criteria. It should aid PCPs in making appropriate early referrals of patients with suspected inflammatory arthritis, accelerating diagnosis and initiation of treatment. Keywords: inflammatory arthritis, rheumatoid, diagnosis, primary care, early referral criteria